PENGEMBANGAN MEDIA PEMBELAJARAN BAHASA ARAB BERBASIS TEKNOLOGI AUGMENTED REALITY (AR) - aziza, ilma fahmi (JIPI (Jurnal Ilmiah Pendidikan Islam), 2024)
The use of technology in education aims to solve problems that occur in the educational process and to achieve several desired goals, and this is in accordance with Miarso's opinion that learning technology is a system created by humans for certain purposes. The goal, which is essentially to make it easier for people to lighten their business.One of the technologies that is contemporary and really supports learning is Augmented Reality (AR) technology. This sophistication is able to provide a new color in the field of education. Its use is not only centered on insight, but also touches the emotional side of students. The experience they feel stimulates their brains to absorb knowledge more progressively.One of the courses that requires interesting learning media is the Arabic language course. This is because this course is one of a group of language courses that requires interactive situations in learning. With learning media that uses Augmented Reality technology, of course this course will become more interactive and interesting.This research is development research whose data comes from interviews, observation and documentation. The data collection methods used were interviews, observation and documentation.Learning using Arabic language learning media based on augmented reality technology was developed using Borg and Gall's product development steps. The research results show that Arabic language learning media based on augmented reality technology is suitable for use and has proven to be effective in learning because it can increase student motivation.